Interlude. The Silencing of Gender-Based Violence - Christelle Rigual (Institut de Hautes Études Internationales et du Développement, 2021)
Gender-based violence (GBV) has been a central area of concern for feminist peace and conflict research and advocacy, yet it was an issue that did not loom large in our research on gender and peacebuilding in Indonesia and Nigeria. In this interlude, we examine the explicit reasons why our project did not focus on questions of GBV, and the silences that exist in our case study locations around the issue. We, further, discuss the ways in which we may have inadvertently contributed to the silencing of narratives of GBV through our approach, and what can be done to try and avoid or minimise these impacts.